MENINGKATKAN KEMAMPUAN PENGENALAN WARNA DASAR MELALUI PERMAINAN LINGKAR WARNA - Pajralnida - (Universitas Negeri Padang, 2016)
Abstract: This research was derived from the inability three students in recognition the primary colours when teaching learning process at class II SLB Work Shop Padang. Based on assessment results and interviews that have done, the resecher found the students are difficult to recognize the primary colour (red, yellow and blue). The purpose of this research is to increase students’ ability in recognition the primary colours through the game colour circumference at class II SLB Work Shop Padang.The kind of this research is action research which is conducted collaborative in peers. Subject three students with the light mental retardation at class II SLB Work Shop Padang. The technique in collecting the data are: observations, discussion and test. Then, will be analyzed by using qualitative and quantitaive.The results showed that: 1) the leraning process in recornizing the primary colours conducted 2 cycles. First, is conducted in 7 meetings and second have done in 4 meetings. 2) the result of the study by using game, there is any increasing. It can be seen from the data before doing the action, AN (0%), KV(15%), and AK (15%). Whereas at the end of cycle 1, AN has increased become 35%), KV(55%), and AK (50%). At the cycle 2, AN has increased (55%), KV(80%), and AK (70%). It can be concluded that the ability of three students have increased after being given this game. Recomended to the teachers and the next researcher to apply game colour cicumference method in class and it can be applied in different materials.Kata Kunci: Pengenalan Warna Dasar, Permainan Lingkar Warna, Anak Tunagrahita Ringan